2019
DOI: 10.1080/15592294.2019.1580111
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy use and breast tissue DNA methylation: analysis of epigenome wide data from the normal breast study

Abstract: Hormone therapy (HT) is associated with increased risk of breast cancer, strongly dependent on type, duration, and recency of use. HT use could affect cancer risk by changing breast tissue transcriptional programs. We hypothesize that these changes are preceded by changes in DNA methylation. To explore this hypothesis we used histologically normal-appearing breast tissue from the Normal Breast Study (NBS). DNA methylation β-values were obtained using the Illumina HumanMethylation 450 BeadChips for 90 samples i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
2
2
Order By: Relevance
“… 61 Changes in gene expression patterns in normal breast tissue after treatment with HT was observed in one experimental study, 62 and a recent study on DNA methylation showed association between HT use and epigenetic changes in normal breast tissue. 63 We did not observe similar changes in our data. Few participants exposed and lack of information on prior HT use, as well as duration of use, could partially explain these results.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“… 61 Changes in gene expression patterns in normal breast tissue after treatment with HT was observed in one experimental study, 62 and a recent study on DNA methylation showed association between HT use and epigenetic changes in normal breast tissue. 63 We did not observe similar changes in our data. Few participants exposed and lack of information on prior HT use, as well as duration of use, could partially explain these results.…”
Section: Discussioncontrasting
confidence: 59%
“…Hall et al found a distinct gene expression profile in breast cancer tissue associated with HT use, and linked HT use to better recurrence‐free survival 61 . Changes in gene expression patterns in normal breast tissue after treatment with HT was observed in one experimental study, 62 and a recent study on DNA methylation showed association between HT use and epigenetic changes in normal breast tissue 63 . We did not observe similar changes in our data.…”
Section: Discussioncontrasting
confidence: 47%
“…These epigenetic modifications triggered by MHT might contribute to BC development and progression. [54] Table 5 summarizes the molecular effectors of MHT contributing to increased BC risk.…”
Section: Molecular and Genetic Effects Of Hormone Replacement Therapy...mentioning
confidence: 99%
“…[ 151 ] Another EWAS illustrated 527 CpG sites with altered levels of DNA methylation in HT users. [ 152 ] Twelve of these loci were all highly significant, such as cg01382688 ( ARHGEF4 ). These findings all confirm that hormone exposure and epigenetic alterations are correlated, providing assistance in the prevention of breast cancer.…”
Section: Four Exemplars Of Ewas Successmentioning
confidence: 99%